Impact of the COVID-19 Pandemic on Liberal Arts Education: An Empirical Study in Hong Kong - Qingyun Li; Youliang Zhang; Kam Wing Cheung; Zhongyang Zhang; King Sun Lam (MDPI AG, 2023)
The COVID-19 pandemic has instigated considerable unprecedented challenges to tertiary education in the aftermath of the mass shutdown of universities across Hong Kong since early 2020. Accordingly, shifting the traditional modalities to the online model has been opted for as the only reasonable alternative in the breakout period. It is, then, essential for educators to perceive the extent to which students' learning attainments and experiences have been negatively impacted by these educational changes in the post-pandemic era. With the aim of examining the abrupt changes which the freshmen students' e-learning experiences and their learning environment have undergone before and after the pandemic, the present quantitative study was conducted at a Liberal Arts Institution in Hong Kong, whose data was collected via the web-based questionnaire FYSLES, or "first-year student learning experience survey". Quantitative analysis of responses indicated that students' impressions and experience of liberal arts education, and students' personalities and skills development, presented a U-shaped trend during the COVID-19 pandemic. The underlying rationale of this study is addressed to higher education policymakers to orient and add value to their safety measures, pertinent recommendations, as well as in context strategies that could be established in view of the pandemic's detrimental effects.